Epidemiology and risk factors of renal cell carcinoma: literature review and correlation according to Lithuanian people epidemiological risk factors - Markevičius, Marius; Jankevičius, Feliksas (Lietuvos chirurgija, 2015)
Background Renal cell carcinoma (RCC) is one of the most dangerous urological cancers. Several risk factors for RCC have been identified, including smoking, obesity, and hypertension. Other risk factors for RCC could be dietary practices (alcohol consumption, food), physical activity, occupational exposures, drugs, other diseases, reproductive and hormonal factors, and others. Results Our literature analysis revealed a high smoking incidence in the past and the present decrease in smoking by 50%. If smoking is a strong causal factor of RCC, in the nearest future, in 10–20 years, we will have a decrease in RCC incidence. In Lithuania, over the last ten years, the prevalence of overweight and obesity among men has increased, and in women it has decreased. The significant reduction in obesity, therefore, would dramatically decrease the incidence of those cancers and lower the mortality rate of RCC in Lithuania. The high prevalence of hypertension and the still low awareness among hypertensive men and women could also be a cause of high incidence of RCC in Lithuania. The Lithuanian population eats many fatty and high- -protein foods. Meat is seen almost in everyday meal, and another unfavorable factor is the low consumption of vegetables, which could be a preventive meal. This problem is seen even in school-age children. Conclusion In the analysis of risk factors and their contribution to the high incidence of RCC in the Lithuanian population, we have found that the main risk factor of RCC is highly frequent in population and could be the main reason of high RCC incidence.